2019
DOI: 10.1016/j.joca.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

In finger osteoarthritis, change in synovitis is associated with change in pain on a joint-level; a longitudinal magnetic resonance imaging study

Abstract: Objective: To investigate determinants of decrease and increase in joint pain in symptomatic finger osteoarthritis (OA) on magnetic resonance (MR) imaging over 2 years. Design: Eighty-five patients (81.2% women, mean age 59.2 years) with primary hand OA (89.4% fulfilling American College of Rheumatology (ACR) classification criteria) from a rheumatology outpatient clinic received contrast-enhanced MR imaging (1.5T) and physical examination of the right interphalangeal finger joints 2e5 at baseline and at follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…Few studies have investigated the longitudinal relationship between inflammatory MRI features and pain in hand OA. Previous studies have shown that in interphalangeal OA, an increase in synovitis was associated with more pain, less synovitis was associated with less pain, and also that fluctuation in BMLs amplified this effect of synovitis on change in pain (9,10). These studies also suggest that BMLs mainly have an additive effect when accompanying synovitis, and that synovitis is the main driver of pain (6,10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have investigated the longitudinal relationship between inflammatory MRI features and pain in hand OA. Previous studies have shown that in interphalangeal OA, an increase in synovitis was associated with more pain, less synovitis was associated with less pain, and also that fluctuation in BMLs amplified this effect of synovitis on change in pain (9,10). These studies also suggest that BMLs mainly have an additive effect when accompanying synovitis, and that synovitis is the main driver of pain (6,10).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that in interphalangeal OA, an increase in synovitis was associated with more pain, less synovitis was associated with less pain, and also that fluctuation in BMLs amplified this effect of synovitis on change in pain (9,10). These studies also suggest that BMLs mainly have an additive effect when accompanying synovitis, and that synovitis is the main driver of pain (6,10). Our study shows that a longitudinal association between inflammatory MRI features and pain on palpation is also present in thumb base OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, we did not ascertain effusion during follow-up while it is possible that effusion is a transient phenomenon [ 3 , 18 ]. However, several studies have shown that baseline inflammatory features such as synovitis and BMLs are of clinical relevance for their association with pain and structural progression [ 3 , 5 , 6 , 19 ], regardless of their possible transient nature [ 20 ]. We think the same applies to effusion and therefore, our results are relevant.…”
Section: Discussionmentioning
confidence: 99%
“…We envision including effusion in the MRI scoring system; our scoring method could serve as a blueprint for this. From an earlier MRI study, we learned that increase/decrease in synovitis was associated with increase/decrease in pain [ 20 ]. We think that especially this last finding is interesting because the association of a decrease in synovitis with a decrease in joint pain makes synovitis a treatment target.…”
Section: Discussionmentioning
confidence: 99%